Airway and parenchyma immune cells in influenza A(H1N1)pdm09 viral and non-viral diffuse alveolar damage - Monique Buttignol; Ruy Camargo Pires-Neto; Renata Calciolari Rossi e Silva; Marina Ballarin Albino; Marisa Dolhnikoff; Thais Mauad (Respiratory Research, 2017)
Abstract Background Diffuse alveolar damage (DAD), which is the histological surrogate for acute respiratory distress syndrome (ARDS), has a multifactorial aetiology. Therefore it is possible that the immunopathology differs among the various presentations of DAD. The aim of this study is to compare lung immunopathology of viral (influenza A(H1N1)pdm09) to non-viral, extrapulmonary aetiologies in autopsy cases with DAD. Methods The lung tissue of 44 patients, was divided in the H1N1 group (n = 15) characterized by severe pulmonary injury due to influenza A(H1N1)pdm09 infection; the ARDS group (n = 13), characterized by patients with DAD due to non-pulmonary causes; and the Control group (n = 16), consisting of patients with non-pulmonary causes of death. Immunohistochemistry and image analysis were used to quantify, in the parenchyma and small airways, several immune cell markers. Results Both DAD groups had higher expression of neutrophils and macrophages in parenchyma and small airways. However, there was a higher expression of CD4+ and CD8+ T lymphocytes, CD83+ dendritic cells, granzyme A+ and natural killer + cell density in the lung parenchyma of the H1N1 group (p < 0.05). In the small airways, there was a lower cell density of tryptase + mast cells and dendritic + cells and an increase of IL-17 in both DAD groups (p < 0.05). Conclusion DAD due to viral A(H1N1)pdm09 is associated with a cytotoxic inflammatory phenotype, with partially divergent responses in the parenchyma relative to the small airways. In non-viral DAD, main immune cell alterations were found at the small airway level, reinforcing the role of the small airways in the pathogenesis of the exudative phase of DAD.